REPRESENTASI VISUAL HEDONISME PADA FILM PARASITE - Adinda Maharani (Institut Seni Budaya Indonesia Bandung, 2021)
Film works can be created from various points of view and methods of production techniques so that they become an interesting unified storyline. Parasite is a film that depicts a new perspective with a fascinating story and plot twist in the context of a film with the issue of social inequality in the modern era. The interesting thing in the film Parasite is the depiction of hedonism by characters from poor families, where people think that poor people cannot become hedonists because of their limited abilities. This study uses a qualitative approach and descriptive method, which describes the social relations of the meaning of hedonism in lower-middle families, in the form of forms, activities, characteristics, changes, relationships, similarities, and differences. The results of the research show that the Parasite film illustrates that poor families can practice hedonism in their lives, so this film becomes a source of representation of the country's progress by presenting a luxurious life. If it is associated with the concept of Roland Barthes, Stone becomes a mythical image in the form of a visual representation of how Korean people believe stones can bring good luck.